PENGARUH RASIO DIAMETER PIPA TERHADAP PERUBAHAN TEKANAN PADA BERNOULLI THEOREM APPARATUS - Aufa, Ahmad; Rubiono, Gatut; Mujianto, Haris (Virtual of Mechanical Engineering Article, 2016)
Bernoulli  theorem  can  applied  to  many  devices  such  as  ventury  tube  in  aoutomotivecarburetor, venturimeter, pitot tube, chimney and aeroplane wings. This research is aimed to get the effect of diameter ratio due to pressure different in Bernoulli theorem apparatus. The research is conduct by experiment using fluid flow circuit.  Diameter ratio is varied as 0,67; 0,50 and 0,33. Fluid flow rate is varied by valve opening arrangement as 45o, 60o, 90o. Measurements are done at7  measurement  point  by  U  type  manometer.  Volume  flow  rate  is  measured  by  flowmeter  and stopwatch.  The  research  shows  that  diameter  ratio  has  effect  due  to  pressure  changes.  theincrease  of  diameter  ratio  tend  to  increase  the  pressure.  Maximum  pressure  is  happen  at  0,67 diameter  ratio;  0,0192  lt/s  volume  flow  rate  at  first  measurement  point.  Minimum  pressure  is happen at 0,33 diameter ratio; 0,0247 lt/s volume flow rate at fifth measurement point.